Financial Reporting Opacity and Expected Crash Risk: Evidence from Implied Volatility Smirks - Kim, Jeong‐Bon; Zhang, Liandong (Contemporary Accounting Research, 2014)
The recent financial crisis has stimulated a renewed interest in understanding the determinants of stock price crash risk (i.e., left tail risk). Recent research shows that opaque financial reports enable managers to hide and accumulate bad news for extended periods. When the accumulated bad news reaches a certain tipping point, it will be suddenly released to the market at once, resulting in an abrupt decline in stock price (i.e., a crash). This study extends this line of research by examining the impact of financial reporting opacity on perceived or expected crash risk. Prominent economists, such as Olivier Blanchard, argue that removing the perception of tail risks (in addition to realized tail risks) is crucial in restoring investor confidence and stabilizing the stock market. Using the steepness of option implied volatility skew as a proxy for perceived crash risk, we find that accrual management, the presence of financial statement restatements, and auditor‐attested internal control weakness are all positively and significantly associated with the level of perceived crash risk. Our results suggest that improving financial reporting transparency is an important mechanism for firms and policymakers to reduce the perception of tail risks and stabilize the stock market.